Pectoralis major injuries in the military: a surveillance approach to reduce an underestimated problem. Issue 4 (5th February 2021) - Hauschild, Veronique D; Grier, TL; Schuh-Renner, A; Forrest, L J; Hirleman, C E; Pinyan, E; Jones, B H
Abstract : Introduction: Multiple studies report increasing cases of surgically treated pectoralis major (PM) muscle and tendon ruptures in military populations. Studies associate this with a growing popularity of weight-training and bench press exercises. Mild-to-moderate non-surgical PM traumas and overuse injuries have not been included in these studies despite evidence that these types of outpatient injuries account for the majority of the military's injury medical burden. Methods: To assess rates of all PM injuries (ruptures, tears, strains, overuse), regardless of form of treatment, a PM injury surveillance definition was derived from International Classification of Disease (ICD) diagnostic codes used in routine US Army injury surveillance. A detailed clinical examination of 2016 Active Duty Army medical records was used to identify ICD codes commonly associated with PM injuries. Cost data were calculated and the definition applied to medical data from 2016 through 2018to assess trends. Results: The estimated incidence of PM cases among soldiers was over 95% greater than if only considering severe surgical cases. Over 96% of army annual PM injury costs (direct medical and indirect from lost labour) were for outpatient services. PM injury incidence rates were not statistically different from 2016 to 2018. Conclusions: The PM injury surveillance definition provides a consistent means to monitor trends over time and evaluate the effectiveness of prevention efforts. PM injuries have a larger military impact than previously recognised and prioritised prevention strategies are needed to reduce them. Future interventions could focus on the bench press given its observed association with PM injuries.